On Mixed Type Duality for Multiobjective Programming Containing Support Functions - Husain, I.; Ahmed, A.; Mattoo, Rumana G. (Journal of Informatics and Mathematical Sciences, 2010)
A mixed type vector dual to a multiobjective programming problem containing support functions is formulated and various duality results are proved under generalized invexity conditions. Special cases are generated from our results.